ANALISIS FAKTOR YANG MEMPENGARUHI MAHASISWA MELANJUTKAN PENDIDIKAN KE PROGRAM STUDI PIPS PASCASARJANA UNIVERSITAS ALMUSLIM - Elisa Maharani; Hariki Fitrah; Sumanti sumanti (STKIP Singkawang, 2025)
This study analyzes the factors influencing students' decisions to pursue postgraduate education, specifically in the Social Sciences Education Study Program (PIPS) at Almuslim University. The primary focus is to identify the role of factors such as motivation for career advancement and educational costs in shaping students' decisions. The research design of this study was survey research using the exploratory approach and factors analysis. The subjects of the study were all students at Social Science Education of postgraduate Program at Almuslim University in period 2023. The findings revealed that the drive to enhance competence and credibility to increase career opportunities is a key motivation for students to continue their education. Career advancement often serves as a significant motivator, especially since a postgraduate degree is frequently regarded as a critical requirement for higher positions. Additionally, the cost of education, both direct and indirect, is shown to be a crucial factor affecting students' decisions. Financial constraints often pose a barrier for those wishing to pursue further studies, although adequate financial support can alleviate such concerns. The study's findings imply the need to improve access to financial support, such as scholarships and education loans, as well as to strengthen policies that promote higher education as a criterion for career advancement. Recommendations are directed to the government and educational institutions to expand scholarship programs and educate students about the importance of postgraduate education for career development.